Regional modulation of a stochastically expressed factor determines photoreceptor subtypes in the Drosophila retina - Thanawala, Shivani U. (2013)
Stochastic mechanisms are sometimes utilized to diversify cell fates, especially in nervous systems. In the Drosophila retina, stochastic expression of the PAS-bHLH transcription factor Spineless (Ss) controls photoreceptor subtype choice. In one randomly distributed subset of R7 photoreceptors, Ss activates Rhodopsin4 (Rh4) and represses Rhodopsin3 (Rh3); counterparts lacking Ss express Rh3 and repress Rh4. In the dorsal third region of the retina, the Iroquois Complex transcription factors induce Rh3 in Rh4-expressing R7s. Here, we show that Ss levels are controlled in a binary On/Off manner throughout the retina, yet are attenuated in the dorsal third region to allow Rh3 co-expression with Rh4. Whereas the sensitivity of rh3 repression to differences in Ss levels generates stochastic and regionalized patterns, the robustness of rh4 activation ensures its stochastic expression throughout the retina. Our findings show how stochastic and regional inputs are integrated to control photoreceptor subtype specification in the Drosophila retina.